Selection, adaptation and advantage. Later-life health and wellbeing of English migrants to Australia. Issue 13 (3rd October 2019) - Vanhoutte, Bram; Loh, Vanessa; Nazroo, James; Kendig, Hal; O'Loughlin, Kate; Byles, Julie
ABSTRACT: This study investigates the long-term impact of English adult migration to Australia by comparing health and wellbeing outcomes in later life of English migrants to their counterparts who remained in England (non-migrants) and to native-born Australians. It traces the influence of selection, adaptation and advantage as three mechanisms that can influence migrant health in later life. The analysis utilises data for a cohort aged 60–64 years from the Australian Life Histories and Health (LHH) survey ( n = 1088), a sub-study of the Australian 45 and Up Study, in combination with a matched cohort from the English Longitudinal Study of Ageing (ELSA) ( n = 1139). Social rather than health characteristics were found to play a role in the selection of English migrants. English migrants reported higher subjective quality of life than English non-migrants, and better physical health than the Australian-born, but their mental health outcomes did not significantly differ from the other cohorts. The comparatively better later-life outcomes for the English migrants can partly be linked to advantage, as they hold higher prestige jobs than the Australian-born at lower levels of education.